PENINGKATAN KEMANDIRIAN PASANGAN BARU MENIKAH TERHADAP UPAYA PENCEGAHAN STUNTING DI DESA TANAH DATAR KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Deswita, Deswita; Yulianto, Yulianto; Aulia, Nur; Hindratni, Findy (Poltekkes Kemenkes Riau, 2024)
Stunting is a problem of chronic malnutrition caused by a lack of nutritional intake over a long period of time, resulting in growth disorders in children, namely the child's height is lower or shorter (stunted) than the age standard. The incidence of stunted children in Riau reached 16,275 people spread across various regency. Indragiri Hulu recorded the incidence of stunted children as many as 831 people, which is the 12th highest in all districts in Riau. The birth of a stunted baby can be prevented from the moment of conception in pregnancy. For this reason, the active role of prospective mothers or newly married couples is needed to prepare for their pregnancy well, ensuring adequate nutritional intake and optimal health care during pregnancy. A young mother is required to be able to ensure success in maintaining health during pregnancy, to be able to care for the pregnancy by consuming adequate nutritional food and to be free from other health problems. For this reason, efforts are needed to increase the knowledge of expectant mothers about stunting, nutrition for pregnant women and regular pregnancy checks. The target of this activity is newly married couples, the activity is carried out in 3 meetings. The result of this community service activity is an increase in the independence of newly married couples in efforts to prevent stunting.